Implementasi Content Based Image Retrieval Untuk Menganalisa Kemiripan Bakteri Yoghurt Menggunakan Metode Latent Semantic Indexing - Meivi Kartikasari; Chaulina Alfianti Oktavia (IC-ITECHS, 2014)
Computer Vision technology can be implemented in a variety of fields. One implementation of computer vision in the field of biology, especially in microorganism. The problems that often exist in determining the characteristics of microorganisms is the use of manual counting technique in comparing and determining the corresponding image with the image that you saved earlier. Content Based Image Retrieval technique (CBIR) is needed in analyzing the similarity between the image-based approach yoghurt bacteria with Latent Semantic Indexing. Similarity analysis is done by means of data collection, preprocessing, feature extraction, calculation and visualization of image similarity retrieval results. From the analysis we can obtain the similarity between the tested image with the microorganism image contained in the database